2015
DOI: 10.1007/s10750-015-2254-9
|View full text |Cite
|
Sign up to set email alerts
|

Limited movement of freshwater mussel fish hosts in a southern US river

Abstract: Organisms that live in flowing water need to compensate for downstream displacement. Mobile animals can compensate for displacement by actively swimming or crawling upstream, while sedentary animals need other means to retain their position. Freshwater mussels (Bivalvia, Unionidae) have limited movement as adults, and juveniles drift downstream after excystment from their host. Mussel larvae are ectoparasites on fish, and it has been assumed that fish move larvae back upstream; however, this has not been teste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 88 publications
0
6
0
Order By: Relevance
“…The species distribution is expected to expand further as climate change alters the thermal regimes of coldwater habitats and opens them to colonization by cool‐water fishes (Shuter & Post, ; Chu et al , ). Micropterus dolomieu play an important role in shaping freshwater communities as top predators with a broad dietary niche (MacRae & Jackson, ), as intermediary hosts and dispersal vectors for aquatic invertebrate species (Kappes & Haase, ; Irmscher & Vaughn, ), and through reproductive facilitation for brood parasitic species (Goff, ). There is considerable conservation concern regarding the effects invading M. dolomieu will have on the biotic communities in these systems (Iguchi et al , ; Vander Zanden et al , ; Carey et al , ).…”
Section: Introductionmentioning
confidence: 99%
“…The species distribution is expected to expand further as climate change alters the thermal regimes of coldwater habitats and opens them to colonization by cool‐water fishes (Shuter & Post, ; Chu et al , ). Micropterus dolomieu play an important role in shaping freshwater communities as top predators with a broad dietary niche (MacRae & Jackson, ), as intermediary hosts and dispersal vectors for aquatic invertebrate species (Kappes & Haase, ; Irmscher & Vaughn, ), and through reproductive facilitation for brood parasitic species (Goff, ). There is considerable conservation concern regarding the effects invading M. dolomieu will have on the biotic communities in these systems (Iguchi et al , ; Vander Zanden et al , ; Carey et al , ).…”
Section: Introductionmentioning
confidence: 99%
“…Gene flow among mussel beds requires sufficient flow for the movement of fish hosts, juveniles, sperm, and/or unattached glochidia. Irmscher and Vaughn (2015) found that the movement of fish hosts in the Little River was restricted during droughts. Thus, lowwater conditions during droughts may restrict gene flow between upstream and downstream populations or decrease upstream population sizes and exacerbate genetic drift.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, higher flows promoted longitudinal movements and refuge use by adult Smallmouth Bass (Todd and Rabeni ), and drought conditions greatly restricted these movements (Hafs et al. ; Irmscher and Vaughn ). Although discharge during our study period fluctuated little, we would hypothesize that discharge is important for movement in other water‐year types given its influence on habitat connectivity and water depth.…”
Section: Discussionmentioning
confidence: 99%
“…Smallmouth Bass movements are especially limited under summer drought conditions (Hafs et al. ; Irmscher and Vaughn ). Home range size is typically smaller in streams than in oligotrophic lakes (Ridgway and Shuter ).…”
mentioning
confidence: 99%